Authenticity and coping behaviors in adolescents - Dillard, Amanda Nicole, author; Lucas-Thompson, Rachel Graham, advisor; Haddock, Shelley, committee member; Harman, Jennifer, committee member (Colorado State University. Libraries, 2016)
The goal of this thesis was to determine the extent to which adolescents' reported level of relational authenticity is associated with the use of adaptive or maladaptive coping behaviors. This study used secondary data analyses using data from a previous study (Wenzel & Lucas-Thompson, 2012), which collected questionnaire responses from 153 adolescent participants who completed a modified version of the Authenticity Inventory 3 (AI-3, Goldman & Kernis, 2006) and the Cognitive Emotion Regulation Questionnaire (CERQ, Garnefsky et al., 2001). A factor analysis revealed three categories of coping behaviors: a) adaptive/optimistic, b) adaptive/realistic, and c) maladaptive. These labels were selected because of past research about the effects of the coping behaviors in each factor. Results revealed a negative association between authenticity and adaptive-optimistic coping behaviors and a positive association between authenticity and maladaptive behaviors. Post hoc analyses, which were completed in an attempt to further understand and explain the findings, revealed negative associations between authenticity and symptoms of depression and anxiety, negative associations between adaptive/optimistic coping behaviors and symptoms of depression and anxiety, and positive associations between maladaptive coping behaviors and symptoms of depression and anxiety. Conclusions: The results from this study emphasize need for further research of authenticity and the use and effectiveness of coping behaviors in adolescents. Results also highlight the difficulty of using 'adaptive' or 'maladaptive' as language to describe or categorize coping behaviors.